A Raman spectroscopic study of the pyrolysis of lactose and tannins. (20th May 2022) - Brehm, Simon; Kraus, Jakob; Himcinschi, Cameliu; Kortus, Jens
Abstract: Lactose and tannin are eco‐friendly alternatives to commonly used binders for carbon‐bonded alumina filters that are applied in steel melt filtration. The investigation of binder pyrolysis is a contribution to understand the production process of these filters. In this work, lactose and the tannins gallic acid, ellagic acid, and tannic acid were investigated by Raman spectroscopy. The tannins were measured in situ in an argon‐filled heating chamber. The transformation of the tannin molecules to a system of amorphous disordered carbon could be observed in the Raman spectra. In addition, the condensed pyrolysis products of the tannins were measured and identified. The Raman spectra were supported by peak positions calculated with density functional theory. Abstract : The pyrolysis of lactose and the three tannins gallic acid, ellagic acid, and tannic acid was studied ex situ and in situ by Raman spectroscopy. The transformation of the substance to amorpous carbon could be observed. Additionally, the pyrolysis temperature range and pyrolysis intermediates were identified.